MENINGKATKAN HASIL BELAJAR TOLAK PELURU MELALUI PERMAINAN TOLAK SASARAN PADA DINDING (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This research is done collaboratively and implemented for 2 cycles. Each cycle consists of four phases, namely: planning, implementation, observation and reflection. The subjects were all students of SD Negeri Class V Kajen 02 totaling 25 students, consisting of 20 boys and 5 girls. Data collection techniques used were observation, interview, practice tests, and documentation techniques are analyzed through quantitative analysis and qualitative analysis. Based on the data obtained in Cycle II, teacher performance has increased to the positive direction of the previous cycle is accompanied by an increase in students' learning activities, which is a percentage increase of 20% (from 65% to 85% increase). Then look at the learning outcomes of the acquisition, the acquisition of the final grade average in the classical and thoroughness percentage increase, ie the first cycle an average increase in the final value of 4.8 points from the initial conditions (increased to 70.9), in Cycle II increase of 12.1 points from Sklus I (rising to 83.0). While the increase in the percentage of completeness in the first cycle was 24% of the initial conditions (increased to 68%) and on the Cycle II increase by 28% from the first cycle (up to 96%)..